Model komunikasi persuasi dalam saluran YouTube kisah tanah jawa (KTJ) (Faculty of Communications Science, Dr. Soetomo University, 2020)
This study aims to uncover the characteristics of metaphysical persuasion found on the YouTube channel Kisah Tanah Jawa (KTJ). Indonesian people are known as people who tend to believe in things that are metaphysical. Meanwhile, KTJ is present as a YouTube channel that is engaged in investigating mystical and mythical stories on the island of Java. Being unique because KTJ which is basically a YouTube channel account, it turns out to have its own charm in forming a metaphysical ideology. This can be seen from the rise of thepresence of regional KTJ warriors (small group) on the island of Java that are sporadically similar in mission, which reveals the story of legend and history in each of its regions. Through Michael Heim’s opinion and understanding, it can be seen that KTJ has the characteristics of virtual reality as an attemp to communicate ideology of cyber culture of consumption society, especially in Java, which includes networked communication, simulation, artificial, telepresence, and immersion. Keywords: Baudrillard; Characteristics; Network Communication; Simulation; Simulacra.